2007
DOI: 10.1002/jez.411
|View full text |Cite
|
Sign up to set email alerts
|

Prey envenomation does not improve digestive performance in western diamondback rattlesnakes (Crotalus atrox)

Abstract: Although the toxic properties of snake venoms have been recognized throughout history, very little is known about the adaptive significance of these powerful mixtures. This study examined the popular hypothesis that prey envenomation enhances digestion by influencing the energetic costs of digestion and assimilation, gut passage time, and apparent assimilation efficiency (ASSIM) in western diamondback rattlesnakes (Crotalus atrox), a species whose venom is recognized for its comparatively high proteolytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 84 publications
3
25
1
1
Order By: Relevance
“…In contrast to our predictions, the duration of the SDA response in these bats was not significantly shorter than duration values reported among mammals, though it was near the shorter durations reported in similarly sized mammals (McCue, 2007;Secor, 2009). Duration values reported here agree well with apparent gut transit times (i.e.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In contrast to our predictions, the duration of the SDA response in these bats was not significantly shorter than duration values reported among mammals, though it was near the shorter durations reported in similarly sized mammals (McCue, 2007;Secor, 2009). Duration values reported here agree well with apparent gut transit times (i.e.…”
Section: Discussioncontrasting
confidence: 82%
“…; Krishnamoorthy et al, 1979) and multiplying the result by 100 (McCue, 2007;Secor and Diamond, 2000).…”
Section: Feeding Trialsmentioning
confidence: 99%
“…Thomas and Pough (1979) showed that mice envenomated with Crotalus atrox venom were digested faster by several species of non-venomous snakes than were nonenvenomated mice, especially at low temperatures. However, McCue (2007) found no venom effects on DE or speed of digestion in C. atrox itself, while Chu et al (2009) have shown that venom has no beneficial impact on DE for Viridovipera gracilis and V. stejnegeri, even at low temperatures. Our relatively low measures of AAE for H. haemachatus support this conclusion, and the emergent trend, so far, is for venomous snakes to have lower efficiencies than do non-venomous ones.…”
Section: Discussionmentioning
confidence: 91%
“…These include T b , sex, meal size, body size, season (Bedford & Christian 2000), thermoregulatory opportunities, the effects of venom (Greenwald & Kanter 1979;McCue 2007;Chu et al 2009), clutch effects (Cox & Secor 2007), life history (Tsai et al 2008) and diet (Britt et al 2006). Generally, DE appears to be relatively insensitive to T b (Greenwald & Kanter 1979;Bedford & Christian 2000) over the 'normal thermal range' but Greenwald and Kanter (1979) and Tsai et al (2008) do report decreased DE at low temperatures in Pantherophis guttatus guttatus (as Elaphe guttata guttata; 208C) and Viridovipera stejnegeri (as Trimeresurus stejnegeri stejnegeri; 158C), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Metalloproteinases in rattlesnake venoms have been suggested to facilitate efficient digestion of prey at suboptimal temperatures or when large prey are consumed (Mackessy, 1988(Mackessy, , 2010a; however, several studies have indicated that envenomation does not increase digestive efficacy (McCue, 2007;Chu et al, 2009). In the case of many rattlesnake species, the extent of SVMP activity in a venom is negatively correlated with overall venom toxicity (Mackessy, 2010a).…”
Section: Digestionmentioning
confidence: 99%